Determination of Oviposition, pH, and Salinity of Aedes aegypti's Breeding Places in Semarang Regency (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Dengue Hemorrhagic Fever (DHF) is still a health problem in Indonesia. This is because DHF can cause decease, and the incidence is always increasing. Vector control efforts in Semarang Regency can be done by knowing mosquito bionomics, so one of the actions can be taken is to modify the environment, so that the Ae. aegypti mosquito feels uncomfortable about our environment. This type of research is pure experimental. In this research, mosquito larva will be the subject to be breeded using water with various degrees of acidity (pH) and salinity, then the ability to reproduce in various water with the pH and salinity levels is observed. The sample used was F1 larva originating from breeding places using ovitrap in Semarang Regency. Based on the results of the study showed that the most preferred container of the Ae. Aegypti mosquito for oviposition is a container made of plastic and can. The most optimal water pH for instar 2 larva breeding is water with a pH of 9, followed by water with a pH of 8 and 7. The most optimal water salinity for instar 2 larva breeding is water with a 0-6gr / l salinity.